CELLULASE FROM TRICHODERMA LONGIBRACHIATUM FUNGUS: A REVIEW - Noor T. Hamdan; Hameed M. Jasim (Scholar Express Journals, 2021)
Biocatalysis involves the utilization of natural catalysts, i.e. enzymes, to perform chemical transformations of organic compounds. Living, whole-cells producing enzyme, or isolated enzymes, are used in biocatalysis. The key advantage of biocatalysis is the specificity of the biocatalyst, which potentially results in high yields of a particular product. New biocatalytic processes are based on the availability of interesting, useful new enzymes, usually obtained by screening for microbes that carry out the desired target reaction. Exploration of extreme environments can provide unique microbial culture collections that can be used in screening for suitable enzymes to perform a desired biocatalytic reaction. These enzymes may then be used as biocatalysts in industrially relevant bioprocesses. Cellulases are industrially important enzymes with a market share of 500 million dollars that is expected to rise to 1.5 billion dollars by 2018. Cellulases play a crucial role in generating sugar feedstock for lignocellulosic based biorefinery platform. In addition, their demand in textile, paper, feed and food industries is rising steadily. However, these industrial applications require thermostable, catalytically highly efficient cellulases for making the processes commercially viable Cellulase has been produced from different organism, mainly fungi, bacteria, and protozoans, but the fungus Trichoderma longibrachiatum was recorded as one of the most important commercial cellulase producers and has been widely used in a variety of industries. Trichoderma longibrachiatum is a soil fungus which often found on dead wood, other fungi, building material and sometimes animals. It is found all over the world but mainly in warmer climates. This review assesses the following topics: Genus Trichoderma , Morphology of Trichoderma spp, Molecular Identification of Trichoderma spp. using ITS regions ,Trichoderma longibrachiatum, Cellulases, Mechanism of cellulose hydrolysis by microorganisms, Cellulolytic Domains, Cultural conditions for the cellulase production, Submerged fermentation (SmF), Solid State fermentation (SSF), General aspects of solid state fermentations, Microorganisms used in solid state fermentations, Advantages of SSF, Lignocellulosic Residues/Wastes as Solid Substrate, Physical mutagenesis using ultraviolet light(UV), Optimizations affecting cellulase production by SSF, Inoculum size, Fermentation medium, Initial pH, Temperature, Incubation time, Moisture content of the substrate, Biotechnological application of cellulose, Food industry, Animal feed industry, Pulp and paper industry Pulp and Paper, Agriculture industry, Biofuel industry, Pharmaceutical industries, waste management, Textile.
Keywords: Cellulase; Trichoderma longibrachiatum; Submerged fermentation; Solid state fermentation